A descriptive case study of instructing the “financial reporting & analysis” course: conventional vs convenient approaches / Amit Shrivastava. - Shrivastava, Amit (Universiti Teknologi MARA Cawangan Selangor, 2016)
The Financial Reporting and Analysis (FRA) course has experienced numerous researches and developments in terms of delivery of the course, selection of topics and case studies for the potential managers since its inception. This case study covers issues related to grading pattern, evaluation and learning through cases, identification and selection of cases, best resources for the cases and the topics to be delivered. It also covers conventional and convenient approaches of the delivery adopted by the instructors. This study describes how cases are to be delivered for better outcomes through a comparison of two classic cases of accounting. This study reflects on innovation (i.e. ‘Class Reflection Notes’) and facilitates the instructors to use it as a powerful tool for teaching and learning. The study suggests on how conventions could be delivered conveniently through an extensive use of the board work and a change in the delivery style of the concepts of accounting.